Psychometric properties of the Technology Device Interference Scale (TDIS) and Technology Interference in Life Examples Scale (TILES) in Spanish-speaking couples’ Relationships - Berzosa-Grande, Pilar; Caba-Machado, Vanessa; Mestre-Bach, Gemma; Testa, Giulia; García-Castrillón, Frank; Rivas-Díez, Raquel; Fernández-Rodríguez, Juan Carlos; González-Fraile, Eduardo (Anales de Psicología / Annals of Psychology, 2026)
Background: Technoference is the disruptions caused by technological devices during personal interactions. Although this phenomenon is widespread, there is a lack of validated tools in Spanish. The Technology Device Interference Scale (TDIS) and the Technology Interference in Life Examples Scale (TILES) assess technoference in couples’ relationships. Methods: An observational study to evaluate their psychometric properties. 997 Spanish adults in long-term relationships completed both scales (TDIS, TILES) and the Dyadic Adjustment Scale (DAS). Results: TDIS and TILES showed satisfactory internal consistency (α = .73 to .91). Their unidimensional structure was confirmed, with invariance analyses supporting use across sex and age for TILES, and partial scalar invariance for TDIS. The TDIS analysis revealed significant differences regarding the age and gender of participants; however, in the case of TILES, these differences were confined to age only. Percentiles of the total score were calculated. Higher levels of technoference were associated with a lower relationship quality. Conclusions: TDIS and TILES are valid and reliable instruments that can effectively measure the impact of technoference on couple relationships in Spanish-speaking populations.
Propiedades psicométricas de la Escala de Interferencia de Dispo-sitivos Tecnológicos (TDIS) y de la Escala de Interferencia de la Tecnolo-gía en Ejemplos de Vida (TILES) en relaciones de pareja hispanohablantes.
Título:Propiedades psicométricas de la Escala de Interferencia de Dispo-sitivos Tecnológicos (TDIS) y de la Escala de Interferencia de la Tecnolo-gía en Ejemplos de Vida (TILES) en relaciones de pareja hispanohablantes.Resumen: Antecedentes: La tecnoferencia se refiere a las interrupciones cau-sadas por dispositivos tecnológicos durante las interacciones personales. Si bien este fenómeno está muy extendido, existe una escasez de herramientas validadas en español. La Escala de Interferencia de Dispositivos Tecnoló-gicos (TDIS) y la Escala de Interferencia de la Tecnología en Ejemplos de Vida (TILES) evalúan la tecnoferencia en las relaciones de pareja. Métodos: Estudio observacional para evaluar sus propiedades psicométricas. 997 adultos españoles con relaciones estables completaron ambas escalas (TDIS, TILES) y la Escala de Ajuste Diádico (DAS). Resultados: La TDIS y la TILES mostraron una consistencia interna satisfactoria (α= .73 a .91). Se confirmó su estructura unidimensional, con análisis de invarianza que respaldan el uso en función del sexo y la edad para la TILES, e invarianza escalar parcial para la TDIS. El análisis de la TDIS reveló diferencias signi-ficativas en cuanto a la edad y el género de los participantes; sin embargo, en el caso de la TILES, estas diferencias se limitaron únicamente a la edad. Se calcularon percentiles de la puntuación total. Los niveles más altos de tecnoferencia se asociaron con una menor calidad de la relación. Conclusio-nes: TDIS y TILES son instrumentos válidos y fiables que permiten medir eficazmente el impacto de la tecnoferencia en las relaciones de pareja en poblaciones hispanohablantes.
Keywords: technoference; couple relationships; psychometric properties; Spanish validation; tecnoferencia; relaciones de pareja; propiedades psicométricas; validación en español